Coronary Inflammation and Plaque Vulnerability: A Coronary Computed Tomography and Optical Coherence Tomography Study - Yuki, Haruhito; Sugiyama, Tomoyo; Suzuki, Keishi; Kinoshita, Daisuke; Niida, Takayuki; Nakajima, Akihiro; Araki, Makoto; Dey, Damini; Lee, Hang; McNulty, Iris; Nakamura, Sunao; Kakuta, Tsunekazu; et al. (Circulation. Cardiovascular imaging, 2023)
Vascular inflammation plays a key role in atherogenesis and in the development of acute coronary syndromes. Coronary inflammation can be measured by peri-coronary adipose tissue (PCAT) attenuation on computed tomography angiography. We examined the relationships between the level of coronary artery inflammation assessed by PCAT attenuation and coronary plaque characteristics by optical coherence tomography. A total of 474 patients (198 acute coronary syndromes and 276 stable angina pectoris) who underwent preintervention coronary computed tomography angiography and optical coherence tomography were included. To compare the relationships between the level of coronary artery inflammation and detailed plaque characteristics, we divided the subjects into high (n=244) and low (n=230) PCAT attenuation groups using a threshold value of -70.1 Hounsfield units. The high PCAT attenuation group, compared with the low PCAT attenuation group, had more males (90.6% versus 69.6%; <0.001), more non-ST-segment elevation myocardial infarction (38.5% versus 25.7%; =0.003), and less stable angina pectoris (51.6% versus 65.2%; =0.003). Aspirin, dual antiplatelet, and statins were less frequently used in the high PCAT attenuation group compared to the low PCAT attenuation group. Patients with high PCAT attenuation, compared with those with low PCAT attenuation, had lower ejection fraction (median 64% versus 65%; =0.014) and lower levels of high-density lipoprotein cholesterol (median 45 versus 48 mg/dL; =0.027). Optical coherence tomography features of plaque vulnerability were significantly more common in patients with high PCAT attenuation, compared to those with low PCAT attenuation, including lipid-rich plaque (87.3% versus 77.8%; =0.006), macrophage (76.2% versus 67.8%; =0.041), microchannels (61.9% versus 48.3%; =0.003), plaque rupture (38.1% versus 23.9%; <0.001), and layered plaque (60.2% versus 50.0%; =0.025). Optical coherence tomography features of plaque vulnerability were significantly more common in patients with high PCAT attenuation, compared with those with low PCAT attenuation. Vascular inflammation and plaque vulnerability are intimately related in patients with coronary artery disease. URL: https://www. gov; Unique identifier: NCT04523194.